Chest X-Ray Description Of Vaccinated And Unvaccinated Covid-19 Patients: Case Study - Mustika Fatimah; Erna Widiarti; Tri Hastuti; Muslimah Putri Utami; Rima Ernia; Rina E. Sitindaon; Devi Susanti; Rizka Muliani (Science Midwifery, 2022)
As Covid-19 cases increase and transmission accelerates, it is more likely that new more contagious variants emerge, may spread more easily. Chest X-Rays examination performed during the Covid-19 pandemic is highly suggestive for severe infection and could be used to determine the diagnosis. The chest X-ray image of unvaccinated Covid-19 patients, at the initial onset appeared normal and could find infiltrates paracardial bilaterally. While chest X-ray image of 5-6 months vaccinated Covid-19 patients, in the first days paracardial and bilateral infiltrates were found as well as bilateral parahillar ground-glass opacity, but in late onset, the infiltrates and ground glass opacity became more widespread and bilateral consolidation was also found.